Phenotypic Colistin Resistance and mcr Genes Presence in Salmonella Serovars Originating from Poultry Farms - Ünal, N; Üvey, M (Journal of the Hellenic Veterinary Medical Society, 2025)
The prevalence of antibiotic resistance in bacteria is a matter of significant concern. Colistin is the last resort for the treatment of infections caused by resistant Enterobacteriaceae bacteria. The mcr genes carried and transferred on the plasmid are responsible for the resistance of the bacteria to colistin. The objective of this study was to determine the resistance of Salmonella strains isolated from environmental samples taken from poultry farms and serologically identified to colistin antibiotic, as well as to investigate the presence of mcr genes in resistant strains. A total of 300 Salmonella strains isolated and identified from poultry farms in Turkey between 2014 and 2018 were subjected to phenotypic resistance testing to colistin using the microdilution method. The presence of mcr genes was evaluated using a multiplex PCR protocol. The antibiotic resistance status of Salmonella isolates with phenotypic resistance to colistin analysed using the Kerby Bauer method. A total of 72 out of 300 Salmonella isolates were found to be phenotypically resistant to colistin. Additionally, resistance to pefloxacin, ampicillin, sulphamethoxasol/trimethoprim, gentamycin, and cefotaxime antibiotics was observed in 34.7%, 5.6%, 4.2%, 2.8%, and 1.4% of isolates, respectively. Furthermore, the Salmonella strains examined in this study did not show any detection of the mcr genes. The results of this study indicate that phenotypic colistin resistance in Salmonella strains isolated from poultry environmental samples is not related to the mcr genes analyzed. The mechanism of resistance may be chromosomal resistance and the mechanisms should be investigated by whole genome analysis.